Distribution of strength training volume into one or two daily sessions and neuromuscular adaptation - Haakkinen, K.; Kallinen, M. (Electromyography and Clinical Neurophysiology, 1994)
Haakkinen et al (1) examined the effects of a normal strength training program (1 session per day) for three weeks and the effects of a strength training program involving 2 sessions per day over the next three weeks, where the same training volume performed for the first 3 weeks was distributed among the 2 sessions. 10 trained female athletes were examined. Measurements included maximal voluntary activation of the leg extensor muscles (average iEMG), cross-sectional area of the quadriceps femoris, and maximal voluntary isometric strength of the leg extensors. FINDINGS: No significant changes took place in any measurements during the first 3 weeks when only 1 session was performed per day. However, during the 3 weeks when 2 sessions were performed per day, significant increases were observed in maximal strength and muscle cross-sectional area. A nonsignificant increase was observed in maximum iEMG. Individual changes in iEMG correlated significantly with individual changes in maximal strength. IMPLICATIONS: Distributing training volume into 2 sessions per day over a 3 week period may increase strength and muscle size over training once per day in trained athletes. Whether such training can be continued for longer periods of time without inducing overtraining remains to be determined. It is important for any athlete deciding to train twice a day that training volume is not increased above what is performed once daily. For example, if an athlete normally trains with weights for an hour a day, then training volume can be split in half to a half hour in the morning and a half hour in the evening; this may allow the athlete to train more intensively in each session due to reduced fatigue and can help the athletes obtain increases in size and strength. It is crucial that the athlete does not increase training volume along with the increase in the number of training sessions per day; otherwise, overtraining will occur.